Mineral Wealth and Equitable Development - Ross, Michael (Washington, DC: World Bank, 2012)
In theory, new mineral wealth should offer governments a chance to boost economic growth and reduce inequality. In practice, it often leads to economic stagnation, civil conflict, and heightened inequality. To avoid these problems, governments must navigate a complex series of economic, social, and political challenges. One of the most difficult challenges is deciding how to deal equitably with the regional or local communities where the extraction occurs. The use of transparency, multi-stakeholder dialogues, and special attention to human rights and security can help reduce these risks.